Potential of Pressmud Waste from Sugar Industry in Brick Manufacturing for Green Business and Sustainability - Mohamad, Maheera; Chong, Khai Lin; Abdul Nasir, Muhammad Hafeez; Abidin, Rahimi; Abu, Noor Hidayah; Razalli, Mohd Rizal; Taib, Che Azlan; Mohd Yusoff, Yuhainis; Chellamuthu, Vignes (SHPMedia Sdn Bhd, 2024)
The construction industry in Malaysia is currently witnessing sustained expansion, as seen by the rising demand for residential properties, commercial structures, and other infrastructures throughout our country. Therefore, the present study seeks to identify suitable materials and proportions for manufacturing lightweight bricks utilizing industrial waste materials. This study investigates the feasibility of using pressmud, a sugarcane refinery waste, as a fine bio-aggregate for the production of construction materials. Binary blended cement-pressmud bricks were formed by mixing Ordinary Portland cement with pressmud at various weights percentages (50%, 40%, 30%, 20%, and 10%). Various experiments were undertaken to investigate and compare the characteristics of pressmud bricks and commercial sand bricks. The experiments focused on density determination and compression tests (standard brick). The compression tests demonstrated that cement-pressmud bricks with a weight ratio of up to 20% exhibited a compatible strength to standard brick, with values ranging from 17.16 MPa to 23.01 MPa. The pressmud bricks exhibited reduced weight, with 10% and 20% variants weighing 17-23% less than the standard brick. Thus, it can be concluded that pressmud possesses significant potential as a bio-aggregate for producing lightweight and cost-effective construction materials when used in appropriate proportions